2010
DOI: 10.1161/circinterventions.109.887406
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic and Functional Evaluation of Bifurcation Lesions Undergoing Percutaneous Coronary Intervention

Abstract: Background-We sought to investigate the mechanism of geometric changes after main branch (MB) stent implantation and to identify the predictors of functionally significant "jailed" side branch (SB) lesions. Methods and Results-Seventy-seven patients with bifurcation lesions were prospectively enrolled from 8 centers. MB intravascular ultrasound was performed before and after MB stent implantation, and fractional flow reserve was measured in the jailed SB. The vessel volume index of both the proximal and distal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
119
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(137 citation statements)
references
References 23 publications
12
119
1
2
Order By: Relevance
“…Stent implantation over a bifurcation lesion with or without subsequent post-dilation might induce geometrical changes of the SB ostium leading to observations of angiographic SB compromise during the procedure. These geometrical changes appear to be the combination of two effects: (i) the straightening of the MB that stretches the SB, and (ii) the displacement of the carina towards the SB because of stent expansion [7][8][9][10]27 , confirming observations of other numerical studies on single patients 26,28 . Although angiographic images might demonstrate a significant lumen compromise, this is rarely accompanied by a haemodynamically significant compromise, as demonstrated by post-implantation FFR measurements of the SB 7 .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Stent implantation over a bifurcation lesion with or without subsequent post-dilation might induce geometrical changes of the SB ostium leading to observations of angiographic SB compromise during the procedure. These geometrical changes appear to be the combination of two effects: (i) the straightening of the MB that stretches the SB, and (ii) the displacement of the carina towards the SB because of stent expansion [7][8][9][10]27 , confirming observations of other numerical studies on single patients 26,28 . Although angiographic images might demonstrate a significant lumen compromise, this is rarely accompanied by a haemodynamically significant compromise, as demonstrated by post-implantation FFR measurements of the SB 7 .…”
Section: Discussionsupporting
confidence: 79%
“…A potential complication of this procedure is the aggravation of side branch (SB) ostial stenosis after stent implantation in the main branch (MB) 1,2 and the associated increased risk of periprocedural myocardial infarction [3][4][5] . SB ostium compromise after PSB has been attributed to plaque shift from the MB into the SB 6 or to the shift of the carina into the SB [7][8][9][10] . Several potential predictors of SB ostium occlusion after MB stenting, including SB lumen diameter 11 , distal bifurcation angle 5,9,12 , MB calcified plaque 13 , SB plaque length 4 and thickness 11…”
Section: Introductionmentioning
confidence: 99%
“…The measurement was performed in the angiographic view in which the foreshortening of the 3 segments was minimal. 7,[12][13][14] …”
Section: Angiographic Analysismentioning
confidence: 99%
“…[5][6][7] Therefore, recent studies have suggested that carina shift may be a more important mechanism of SBo compromise. [8][9][10][11] Unfortunately, there have been few systemic studies on relative contribution of carina shift and plaque shift using direct evaluation of SB. The aim of our study was to investigate the mechanism of aggravation of SB ostial stenosis after MV stent implantation in coronary bifurcation lesions by volumetric IVUS analysis of both MV and SBo.…”
mentioning
confidence: 99%